Defective covalent organic framework material as well as preparation method and application thereof

By designing the defective covalent frame material containing the anchor -based anchoring point containing the anchoring point of the anchoring point, the three components of the three components and the post -decoration response method are used to solve the existing solid -state electrolytic materials in terms of lithium ion conduction performance, stability and compatibility. Insufficient, the chemical and thermodynamic stability of the efficient lithium ion conduction and the chemical and thermodynamic stability.

CN119350564AActive Publication Date: 2025-01-24EAST CHINA JIAOTONG UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411466858.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

Existing solid electrolyte materials have shortcomings in lithium ion conduction performance, stability and compatibility, and it is difficult to meet the high safety and high energy density requirements of lithium ion batteries.

Method used

By designing the defective co -price organic framework material containing the anchoring point of the aldehyde base, use the three components to concentrate the reaction and the post -decoration reaction method to introduce functional small molecules to improve lithium ion conduction performance.

Benefits of technology

The prepared functional co -price organic framework materials have excellent lithium ion conduction performance, chemistry and thermodynamic stability, and are suitable for the application of solid electrolyte materials, which improves the safety and energy density of lithium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350564A_ABST
    Figure CN119350564A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a defective covalent organic framework material. The prepared defective covalent organic framework has high porosity, good crystallinity and thermal stability, the pore wall of the framework contains an active anchoring point which can be modified after functionalization, and the defective covalent organic framework has good universality in methodology for constructing the defective covalent organic framework. The preparation method comprises the following steps: preparing a defective covalent organic framework material containing an active anchoring point based on a three-component copolycondensation strategy, and introducing functional small molecules through a post-modification reaction to obtain the covalent organic framework-based solid electrolyte material with good lithium ion conduction performance. The material has good lithium ion transmission performance in a temperature interval from room temperature to 80 DEG C. The excellent performance proves that the defective covalent organic framework material provided by the invention is a parent material which has good universality and can be subjected to post-modification functionalization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of covalent organic frameworks, and in particular relates to the preparation of a defective covalent organic framework material containing aldehyde active anchoring points and its application in solid electrolytes. Background Art

[0002] Lithium-ion batteries are composed of a positive electrode, a negative electrode, and a diaphragm soaked in an organic electrolyte. The electrolyte is a bridge connecting the positive and negative electrode materials, and plays the role of transporting and conducting current between the positive and negative electrodes of the battery. As the only liquid component in lithium-ion batteries, it itself has problems such as flammability, easy decomposition at high temperatures, and corrosiveness, which seriously hinders the development of lithium-ion batteries into safe solid devices, resulting in the loss of the possibility of obtaining high safety, high mechanical strength and high reliability. In recent years, solid-state lithium batteries with solid electrolytes as core components have been widely regarded as the key to the next generation of energy storage technology due to their advantages such as high safety, high energy density, long cycle life, good rate performance and wide operating temperature range.

[0003] At present, the reported solid electrolytes mainly include two categories: inorganic solid electrolytes and polymer solid electrolytes. Although inorganic solid electrolytes have been successfully applied to the field of batteries, there are still some problems, such as large interface impedance after the electrolyte contacts lithium metal, poor compatibility with positive and negative electrodes, low lithium ion conductivity and poor stability in the air, which reduces the battery performance. Polymer electrolyte materials have the advantages of good processing performance, light weight, and good viscoelasticity, but this type of electrolyte material has excellent crystallization performance, poor ion conductivity when the material is not heat-treated, and its ion transport area is mainly concentrated in the amorphous area. The relationship between the structure and performance of the electrolyte material cannot be clearly defined. Therefore, how to prepare solid electrolyte materials with good stability and high lithium ion conductivity through reasonable molecular structure design will help further promote the development of lithium-ion batteries.

[0004] In order to prepare solid electrolyte materials with excellent lithium ion conductivity, the material structure design needs to meet the following two basic conditions: 1) Excellent lithium ion conductivity requires the material itself to have good skeleton segment regularity and certain mobility; 2) The material itself needs to carry certain positive and negative charges to improve the degree of ion dissociation. Compared with traditional polymers, covalent organic frameworks (COFs) are a class of organic porous polymers with excellent crystallinity. They are designed and made based on the principles of dynamic covalent chemistry. In the process of reversible dynamic covalent bonds continuously forming and breaking bonds, a long-range ordered porous structure is formed. In addition, COFs materials not only have the advantages of light weight, strong structural designability, and excellent material stability, but also their ordered pore structure can provide a broad modification space for active molecules, and can also provide specific transportation paths for lithium ion conduction and migration, making COFs materials a research hotspot for designing new solid electrolyte materials. Although there have been several reports of fixing anionic groups on the COFs framework through the "bottom-up method" and "post-modification method" to improve lithium ion conductivity, the ionic groups themselves are easy to be free, and the flexibility of the ionic segments is greatly restricted, so it is difficult to introduce or fix anionic groups on the COFs framework, making this strategy difficult to be widely used and promoted in the field of solid electrolytes. Therefore, how to effectively fix anionic groups on the COFs framework has become a key link in the preparation of COFs-type solid electrolyte materials.

[0005] The functionalization reaction method in the post-modification method is widely used to regulate the structure and function of COFs materials. This method can ensure the stability of the framework structure while introducing functional groups (anionic groups) and is considered to be the most effective method for introducing functional groups. Generally speaking, for COFs materials to undergo functionalization reactions, it is necessary to reserve functional groups that can undergo the next chemical reaction in the framework structure as anchor points for post-modification reactions (such as acetylene, hydroxyl, amine, olefin, azide and nitrile). Among them, amino groups in nucleophilic functional groups can undergo mild reactions with aldehyde groups and simple post-treatment Schiff base reactions, which are ideal for COFs functionalization reactions. In recent years, the Bein, Loh and Dong research groups have prepared COFs materials containing amino active anchor points through a two-step reaction method or a precise screening of reaction solvent systems. However, during the reaction and preparation of COFs materials, the active anchor point functional groups tend to combine with structural units or inhibit the formation of COFs crystals. Therefore, it is still a big problem to introduce or reserve nucleophilic functional groups in the COFs framework. Summary of the invention

[0006] In view of the above-mentioned prior art, the present invention provides a preparation method of a defective covalent organic framework material containing aldehyde active anchoring points and its application in solid electrolytes.

[0007] In order to solve the above technical problems, the present invention proposes a defective covalent organic framework material, which includes components of C3 type aldehyde organic monomer, C3 type amino organic monomer and unilateral amino organic monomer, the functional group molar ratio of the C3 type aldehyde organic monomer to the C3 type amino organic monomer and the unilateral amino organic monomer is 1:1, the functional group molar ratio of the C3 type amino organic monomer to the unilateral amino organic monomer is 4:1-2:3, and the covalent organic framework material is prepared based on a three-component co-condensation reaction; the pore size distribution of the covalent organic framework material is 1.0-5.0nm, the specific surface area is 60-800m 2 g -1 .

[0008] Furthermore, the defective covalent organic framework material of the present invention comprises:

[0009] The C3 type aldehyde organic monomer is 1,3,5-tri(p-formylphenyl)benzene or 2,4,6-tri(4-aldehydephenyl)-1,3,5-triazine; the C3 type amino organic monomer is 1,3,5-tri(4-aminophenyl)benzene; the unilateral amino organic monomer is one of aniline, 4-aminobiphenyl, 3',5'-diphenylbiphenyl-4-amine, and 5-phenyl-[1,1:3,1-terphenyl]-4,4-diamine.

[0010] In the three-component co-condensation reaction, the mixed solvent used is an organic solvent that can mix the above three organic monomers to form a uniform dispersion, and the organic solvent is a combination of one or more of dioxane, n-butanol / o-dichlorobenzene and mesitylene / dioxane; the catalyst is an acetic acid aqueous solution with a molar concentration of 3M to 9M.

[0011] At the same time, the present invention also proposes a method for preparing the above covalent organic framework material, comprising the following steps:

[0012] Step 1) weighing the molar ratio of each component functional group of the C3 type aldehyde organic monomer, the C3 type amino organic monomer and the unilateral amino organic monomer, and weighing the mixed solution and the catalyst according to the molar volume concentration of the total amount of organic monomer and the mixed solvent and the total amount of organic monomer and the catalyst are 1mmol / mL respectively;

[0013] Step 2) The three organic monomers and the mixed solvent weighed in step 1) are placed in an ampoule, mixed evenly under ultrasonic conditions, and then the catalyst weighed in step 1) is added to carry out a polycondensation reaction based on a three-component co-condensation strategy through a solvent thermal reaction to prepare a defective covalent organic framework material containing aldehyde active anchor points.

[0014] Furthermore, the preparation method of the present invention, wherein:

[0015] In step 2), the process conditions of the solvent thermal reaction are: reacting in an oven, the reaction temperature is 90-150°C, the reaction time is 24-96 hours, and after the reaction is completed, a precipitate is obtained at the bottom of the ampoule bottle, and the precipitate is subjected to post-treatment reaction to obtain a defective covalent organic framework material containing an aldehyde active anchor point. The post-treatment process is: cooling the precipitate to room temperature, collecting the precipitate with a centrifuge tube, and then washing it with tetrahydrofuran, methanol and acetone for multiple times until the solution is colorless, and the product obtained by drying is a yellow solid powder; purifying by Soxhlet extraction, extracting with tetrahydrofuran for 12-96 hours, and then vacuum drying the obtained polymer for 24-48 hours.

[0016] In step 2), in the solvent thermal reaction, preferably, the reaction temperature is 120° C. and the reaction time is 72 hours.

[0017] In step 2), in the purification by Soxhlet extraction, preferably, the extraction time using tetrahydrofuran is 24 hours, and the obtained polymer is vacuum dried for 24 hours.

[0018] The present invention proposes to use the defective covalent organic framework material prepared by the above preparation method to prepare a solid electrolyte material. The method is: functionalization modification of the defective covalent organic framework material is performed based on a functionalization reaction method, a functional covalent organic framework material is prepared by Schiff base reaction and ion exchange reaction in sequence, and the solid electrolyte material is prepared by a tabletting method on the activated functional covalent organic framework material.

[0019] Furthermore, the defective covalent organic framework material is functionally modified based on a functionalization reaction method. The defective covalent organic framework material is used as a matrix, and a functional small molecule 3-aminopropane sulfonic acid with an amino functional group is introduced through a Schiff base reaction. The functional small molecule is used as a molecular group for improving lithium ion conduction. The sulfonic acid group is exchanged into a lithium sulfonate group through an ion exchange reaction to obtain a functional covalent organic framework material. The steps are as follows:

[0020] The defective covalent organic framework material and the functional small molecule are added to a reaction bottle at a molar ratio of 1:1.2, and an appropriate amount of anhydrous ethanol is added as a reaction solvent, and the mixture is heated to 80°C for reaction for 12 hours, and the precipitate is collected with a centrifuge tube, and the unreacted functional small molecules are removed by washing with ethanol for multiple times, and then dried to obtain a bright yellow solid powder intermediate product;

[0021] The intermediate product and a 5M LiOAc aqueous solution were added to a reaction bottle at a mass volume ratio of 50 mg / 20 ml, and stirred at room temperature for 72 hours. After the reaction was completed, the precipitate was collected, centrifuged and washed with deionized water several times, and the yellow solid powder obtained by drying was the functional covalent organic framework material.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The present invention provides a method for preparing a defective covalent organic framework (COFs) material containing an aldehyde active anchor point. Fig.17 The synthesis route is shown. The functional small molecules are efficiently introduced in the post-modification reaction by reacting the aldehyde anchoring points in the defective COFs material with the amino groups in the functional small molecules through Schiff base reaction. Fig.18 The post-modification functionalization reaction scheme is shown to achieve efficient preparation of functional COFs materials.

[0024] (2) The defective COFs (TPT-TPB-DCOF-X) provided by the present invention have the advantages of good chemical and thermodynamic stability, large specific surface area, and ordered one-dimensional channels.

[0025] (3) The solid electrolyte material prepared by the functional COFs material provided by the present invention has excellent lithium ion conductivity in a wide temperature range.

[0026] (4) The preparation method of the present invention has the advantages of convenience, simplicity, good methodological universality, etc., and can provide reliable parent materials and important reference value for the preparation of functional COFs materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 FT-IR result of TPT-TPB-DCOF-X prepared in Example 1;

[0028] Figure 2 This is the TGA result of TPT-TPB-DCOF-X prepared in Example 1;

[0029] Figure 3 The XRD result of TPT-TPB-DCOF-X prepared in Example 1;

[0030] Figure 4 The TPT-TPB-DCOF-60 prepared in Example 1 13 C-SNMR results;

[0031] Figure 5 This is the SEM result of TPT-TPB-DCOF-60 prepared in Example 1;

[0032] Figure 6 FT-IR result of TPB-DCOF-X prepared in Example 2;

[0033] Figure 7 This is the TGA result of TPB-DCOF-X prepared in Example 3;

[0034] Figure 8 The XRD result of TPB-DCOF-X prepared in Example 4;

[0035] Fig. 9 The TPB-DCOF-60 prepared in Example 5 13 C-SNMR results;

[0036] Fig.10 This is the SEM result of TPB-DCOF-60 prepared in Example 2;

[0037] Fig.11 The porous properties of TPT-TPB-DCOF-X prepared in Example 1;

[0038] Fig.12 The porous properties of TPT-TPB-DCOF-X prepared in Example 1;

[0039] Fig.13 This is the EIS result of the solid electrolyte TPT-TPB-DCOF-60-SO3Li prepared in Example 6;

[0040] Fig.14 The EIS results of the solid electrolyte TPT-TPB-DCOF-60-SO3Li prepared in Example 6 before and after current polarization;

[0041] Fig.15 The time-current results before and after polarization of the solid electrolyte TPT-TPB-DCOF-60-SO3Li prepared in Example 6;

[0042] Fig.16 It is the LSV result of TPT-TPB-DCOF-60-SO3Li in the present invention;

[0043] Fig.17 A schematic diagram of the synthesis of TPT-TPB-DCOF-X and TPB-DCOF-X provided by the present invention;

[0044] Fig.18 This is a post-modification functionalization reaction circuit diagram provided by the present invention. DETAILED DESCRIPTION

[0045] The design concept of the preparation method of the defective covalent organic framework material proposed in the present invention is: the aldehyde anchor point is used as a nucleophilic group, which is easy to carry out functional post-modification reaction. In addition to excellent porosity and stability, the functional modification on the COFs skeleton gives the material good structural controllability and ordered ion channels, showing application prospects in the field of solid electrolyte materials. Through a three-component co-condensation strategy, a defective COFs material containing defects and active anchor points is prepared with a unilateral organic monomer as an end-capping group. The present invention first prepares a defective covalent organic framework material containing an active anchor point based on a three-component co-condensation strategy, and then introduces functional small molecules through a post-modification reaction to obtain a covalent organic framework-based solid electrolyte material with good lithium ion conductivity. The material has good lithium ion transport performance in the temperature range of room temperature to 80°C. These excellent properties confirm that the defective covalent organic framework material provided by the present invention is a type of matrix material with good universality and can be post-modified and functionalized. Fig.17 The circuit diagram of the synthesis of defective covalent organic framework materials provided by the present invention is shown. Fig.18 A post-modification functionalization reaction scheme is shown.

[0046] In the present invention, the defective COFs material includes components including C3 type aldehyde organic monomer, C3 type amino organic monomer and unilateral amino organic monomer, the molar ratio of the functional groups of the C3 type aldehyde organic monomer to the C3 type amino organic monomer and the unilateral amino organic monomer is 1:1, the molar ratio of the functional groups of the C3 type amino organic monomer to the unilateral amino organic monomer is 4:1-2:3, and is prepared based on the three-component co-condensation reaction; the pore size distribution of the covalent organic framework material is 1-500nm, the specific surface area is 10-2500m 2 g -1 .

[0047] In the present invention, COFs materials with good stability and high porosity are prepared by designing COFs monomers and using a solvothermal method. At the same time, the prepared COFs pore walls have aldehyde anchor points that can be used for functional post-modification, showing good universality in the methodology of constructing defective covalent organic frameworks. The solid electrolyte material prepared by the functional COFs material provided by the present invention has good lithium ion transmission performance in the temperature range of room temperature to 80°C.

[0048] The organic monomer contains a unilateral amino group-related group, such as any one or a combination of at least two of aniline, 4-aminobiphenyl, 3',5'-diphenylbiphenyl-4-amine, and 5-phenyl-[1,1:3,1-terphenyl]-4,4-diamine, and the preferred unilateral amino group is 3',5'-diphenylbiphenyl-4-amine.

[0049] The organic monomers include any one or a combination of at least two of the organic monomers having a C3 configuration, preferably 1,3,5-tris(4-aminophenyl)benzene, 1,3,5-tris(p-formylphenyl)benzene and 2,4,6-tris(4-formylphenyl)-1,3,5-triazine;

[0050] In the three-component co-condensation reaction, the mixed solvent is an organic solvent that can mix the three organic monomers to form a uniform dispersion, and the organic solvent is a combination of one or more of dioxane, n-butanol / o-dichlorobenzene and mesitylene / dioxane. Preferably, the catalyst is mesitylene / dioxane.

[0051] In the three-component co-condensation reaction, the catalyst is an aqueous solution of acetic acid with a molar concentration of 3M to 9M. Preferably, the catalyst is a 6M aqueous solution of acetic acid;

[0052] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer is not specified in the instruments used, they are all conventional products that can be purchased through regular channels. The chemical raw materials used in the present invention can be easily purchased in the domestic chemical product market.

[0053] Example 1

[0054] The synthesis method of defective COFs material (TPT-TPB-DCOF-X) is as follows: Fig.17 As shown, the process is as follows:

[0055] Step 1) In a 10 mL glass tube, add C3 structural unit monomers 2,4,6-tris(4-formylphenyl)-1,3,5-triazine and 1,3,5-tris(4-aminophenyl)benzene and end-capping structural unit monomer 3',5'-diphenylbiphenyl-4-amine. Specific amounts are shown in Table 1.

[0056] Table 1 Amount of each organic monomer used in the synthesis of defective TPT-TPB-DCOF-X

[0057]

[0058] Step 2) After adding the above three organic monomers, add a mixed solvent (mesitylene / dioxane / 6M acetic acid aqueous solution (1.0 / 1.0 / 0.2mL)), wherein mesitylene and dioxane are organic solvents that can mix the above three organic monomers to form a uniform dispersion, and 6M acetic acid aqueous solution is used as a catalyst in the three-component co-condensation reaction. Mix and ultrasonicate for 10 minutes to mix the monomers evenly. In Table 1, X=20, X=40, and X=60 correspond to the synthesized defective COFs material samples TPT-TPB-DCOF-20, TPT-TPB-DCOF-40, and TPT-TPB-DCOF-60, respectively. Freeze with liquid nitrogen, evacuate and fill with nitrogen for 10 minutes each (repeat three times), seal the tube with a flame gun under vacuum, and react in an oven at 120°C for 3 days. After the reaction is completed, the mixture is cooled to room temperature, and the precipitate is collected with a centrifuge tube, and then washed with tetrahydrofuran, acetone and methanol for multiple times until the aqueous solution is colorless, and the product obtained by drying is a yellow solid powder. Subsequently, the obtained yellow solid powder is further purified by Soxhlet extraction, extracted with tetrahydrofuran for 24 hours, and then the obtained product is vacuum dried for 24 hours.

[0059] The yields were determined by the chemical reaction yield calculation method and were 87%, 86% and 85% (X=20, X=40 and X=60), respectively. Figure 1 FTIR spectrum of TPT-TPB-DCOF-X material at 1620 cm -1 The stretching vibration characteristic peak of -C=N- indicates the formation of imine bond of COFs material. -1 and 2850cm -1 At , the stretching vibration peaks of -C=O- and CH bond in the aldehyde group of the active anchor point can be observed, respectively, indicating the existence of the aldehyde anchor point. Figure 2 The TGA data of TPT-TPB-DCOF-X material is shown in the figure. It can be seen from the figure that the material has good thermal stability. Figure 3 ) characterizes the crystallization properties of the material. Figure 3 It can be obtained that diffraction peaks appear at 4.0°, 6.8°, 7.9°, and 10.4°, corresponding to the crystal planes of (100), (110), (200), and (210). A strong diffraction peak appears at the 4.0° position, indicating that the material has good crystallinity. Figure 4 Solid-state NMR of TPT-TPB-DCOF-60 material 13 C spectrum, with a -C=N- carbon peak at 162ppm, further illustrates the formation of characteristic connecting bonds of COFs materials. Figure 1 The infrared spectrum data in are consistent. Figure 5 The SEM electron microscope image of TPT-TPB-DCOF-60 material shows that the material is a typical two-dimensional material structure. The above data show that the TPT-TPB-DCOF-X material was successfully prepared.

[0060] Example 2

[0061] The synthesis method of defective COFs material (TPB-DCOF-X) is as follows:

[0062] Step 1) In a 10 mL glass tube, C3 structural unit monomers 1,3,5-tri(p-formylphenyl)benzene and 1,3,5-tri(4-aminophenyl)benzene and end-capping structural unit monomer 3',5'-diphenylbiphenyl-4-amine were added. The specific amounts are shown in Table 2.

[0063] Table 2 The amount of each organic monomer used in the synthesis of defective TPB-DCOF-X

[0064]

[0065] Step 2) is the same as step 2) of Example 1, and the final product is a yellow solid powder. In Table 2, X=20, X=40, and X=60 correspond to the synthesized defective COFs material samples TPB-DCOF-20, TPB-DCOF-40, and TPB-DCOF-60, respectively.

[0066] After measurement, the yields were 89%, 87% and 88% (X=20, X=40 and X=60), respectively. Figure 6 FTIR spectrum of TPB-DCOF-X material at 1618 cm -1 The stretching vibration characteristic peak of -C=N- indicates the formation of imine bond of COFs material. -1 and 2855cm -1 At , the stretching vibration peaks of -C=O- and CH bond in the aldehyde group of the active anchor point can be observed, respectively, indicating the existence of the aldehyde anchor point. Figure 7 The TGA data of TPB-DCOF-X material shows that the material has good thermal stability and the material decomposes significantly at around 450°C. XRD test characterizes the crystallinity of the material, such as Figure 8 As shown, diffraction peaks appear at 4.0°, 6.8°, 7.9°, and 10.4°, corresponding to the (100), (110), (200), and (210) crystal planes. A strong diffraction peak appears at the 4.0° position, indicating that the material has good crystallinity. Fig. 9 Solid-state NMR of TPB-DCOF-60 material 13C spectrum, with a -C=N- carbon peak at 160 ppm, further illustrates the formation of characteristic connecting bonds of COFs materials. Figure 6 The infrared spectrum data in are consistent. Fig.10 This is the SEM electron microscope image of TPB-DCOF-60 material, which is a typical two-dimensional material structure. The above data show that TPB-DCOF-X material was successfully prepared.

[0067] Example 3

[0068] Preparation of functional COFs material TPT-TPB-DCOF-60-SO3Li.

[0069] The defective COFs material TPT-TPB-DCOF-60 prepared in Example 1 has a framework pore wall containing abundant aldehyde functional groups as anchor points for post-modification reactions. The defective covalent organic framework material is functionally modified based on a functionalization reaction method. The defective covalent organic framework material is used as a matrix, and a functional small molecule 3-aminopropane sulfonic acid with an amino functional group is introduced through a Schiff base reaction. The functional small molecule serves as a molecular group for enhancing lithium ion conduction, and the sulfonic acid group is converted into a lithium sulfonate group through an ion exchange reaction. Fig.18 The post-modification functionalization reaction route is shown.

[0070] The preparation process of TPT-TPB-DCOF-60-SO3Li is as follows:

[0071] In a 50 mL reaction bottle, 68.83 mg (0.01 mmol) of the parent material TPT-TPB-DCOF-60 was added, followed by 10.08 mg (0.012 mmol) of the functional small molecule 3-aminopropane sulfonic acid and 20 mL of anhydrous ethanol as the reaction solvent. The mixture was heated to 80 ° C and reacted for 12 h. The product was collected in a centrifuge tube, washed with ethanol several times to remove the unreacted small molecules, and dried to obtain a bright yellow solid powder, which was recorded as TPT-TPB-DCOF-60-SO3H, with a yield of 94%.

[0072] Add 50 mg of TPT-TPB-DCOF-60-SO3H to a reaction bottle, then add 20 ml of 5M LiOAc aqueous solution, stir at room temperature for 3 days. After the reaction is completed, collect the precipitate, centrifuge and wash it with deionized water several times, and dry it to obtain a yellow solid powder, which is the functional COFs material TPT-TPB-DCOF-60-SO3Li, with a yield of 88%.

[0073] Example 4

[0074] The pore performance of the defective COFs materials prepared in Example 1 and Example 2 was analyzed.

[0075] Fig.11 It is shown that at 77K, the N2 adsorption isotherms respectively determine that the specific surface areas of the defective COFs materials TPT-TPB-DCOF-X synthesized in Example 1 are 762m 2 g -1 、691m 2 g -1 and 570m 2 g -1 (corresponding to TPT-TPB-DCOF-20, TPT-TPB-DCOF-40 and TPT-TPB-DCOF-60 respectively). Fig.12 It is shown that at 77K, the N2 adsorption isotherms respectively determine that the specific surface areas of the TPB-DCOF-X materials synthesized in Example 2 are 91m 2 g -1 、83m 2 g -1 and 67m 2 g -1 (Corresponding to TPT-TPB-DCOF-20, TPT-TPB-DCOF-40 and TPT-TPB-DCOF-60 respectively) The defective COFs material prepared by the present invention has a large specific surface area, and can provide more active sites in the process of lithium ion transmission, enhance the interaction between the active sites and lithium ions, and improve the transmission capacity of lithium ions. The adsorption NLDFT fitting model shows that the pore size distribution range of TPT-TPB-DCOF-X and TPB-DCOF-X synthesized according to Example 1 and Example 2 is mainly in the range of 1-5nm (Table 3 is the pore performance analysis of Example 1 and Example 2). The pore size distribution of the defective COFs material prepared in Example 1 and Example 2 is in the range of 1-2nm, while the atomic radius of lithium ions is 0.76nm. The pore size distribution range of the defective COFs material can provide an effective channel for the free transmission of lithium ions in the pores. In addition, defective COFs materials have good crystallinity and high order. Their ordered structure provides a good transmission environment for the rapid transmission of lithium ions within the pores of COFs materials, showing excellent potential in the process of rapid lithium ion transmission.

[0076] Table 3 Pore performance analysis of NH2-CTF-1 and NH2-CTF-2

[0077] polymer <![CDATA[S BET (m 2 g -1 )]]> <![CDATA[V total (cm 3 g -1 )]]> Pore ​​size (nm) TPT-TPB-DCOF-20 762 0.45 1.27 TPT-TPB-DCOF-40 691 0.41 1.27 TPT-TPB-DCOF-60 570 0.39 1.27 TPB-DCOF-20 91 0.12 1.26 TPB-DCOF-40 83 0.11 1.26 TPB-DCOF-60 67 0.09 1.26

[0078] Example 5

[0079] The degree of polymerization of the functional COFs material (TPT-TPB-DCOF-60-SO3Li) prepared in Example 3 was investigated.

[0080] The elemental analysis method was used for characterization. From the data in Table 4, it can be seen that the actual measured values ​​of the three elements C, N, and H in the functional COFs material TPT-TPB-DCOF-60-SO3Li are close to the theoretical content, indicating that the degree of polymerization of the material is very high.

[0081] Table 4 Elemental analysis results of TPT-TPB-DCOF-60-SO3Li

[0082] C(%) N(%) H(%) Theoretical content 73.72 9.26 4.68 Experimental content 71.95 8.64 4.35

[0083] Example 6

[0084] The functional COFs material (TPT-TPB-DCOF-60-SO3Li) prepared in Example 3 was used to prepare a solid electrolyte material by a tableting method.

[0085] The specific operation steps are as follows: In a glove box with a nitrogen atmosphere, the activated TPT-TPB-DCOF-60-SO3Li powder (50 mg) is pressed into tablets using a press with a pressure of 15 MPa for 5 min. The disc in the mold is then removed for electrochemical performance testing.

[0086] Test of the lithium ion conductivity of the above solid electrolyte material: The lithium ion conductivity of the solid electrolyte material is tested by using an electrochemical workstation and characterized by electrochemical impedance spectroscopy (EIS). The test temperature is between 30 and 80°C, and the temperature interval is tested every 10°C. The bulk resistance of the solid electrolyte material is obtained by the intersection of the AC impedance spectrum and the real axis, and its ion conductivity at different temperatures is calculated. The ion conductivity calculation formula is shown below.

[0087]

[0088] Wherein: L, S and R represent the thickness of the solid electrolyte material disc, the area of ​​the disc and the bulk resistance of the solid electrolyte material respectively.

[0089] Fig.13 is the EIS spectrum of the solid electrolyte material under the test conditions of 30 to 80 °C. According to the above ion conductivity calculation formula, the lithium ion conductivity of TPT-TPB-DCOF-60-SO3Li from 30 to 80 °C is 2.95×10 -5 ,4.06×10 -5 ,6.17×10 -5 ,1.05×10 -4 ,1.59×10 -4 and 2.56×10 -4 S cm-1 Compared with the reported COFs-type solid electrolytes, TPT-TPB-DCOF-60-SO3Li exhibits excellent lithium ion conductivity and shows great application potential in solid electrolyte materials.

[0090] Example 7

[0091] In order to further verify the practicality of the solid electrolyte material, the lithium ion migration number and electrochemical stability window of the material were tested. For the solid electrolyte material (TPT-TPB-DCOF-60-SO3Li) prepared in Example 6, the lithium ion migration number was obtained by assembling a symmetrical battery Li / TPT-TPB-DCOF-60-SO3Li / Li, polarizing the symmetrical battery with a DC voltage, and testing the EIS spectra and polarization current-time curves before and after polarization. The linear sweep voltammetry (LSV) curve was used to test the electrochemical stability window of the electrolyte material. This test is used to characterize the stability of the material under high voltage test conditions. Using the classic Vincent method, the lithium ion migration number of the TPT-TPB-DCOF-60-SO3Li material was calculated to be 0.82±0.02, as shown Fig.14 and Fig.15 As shown. Before 4.54V, the oxidation current of TPT-TPB-DCOF-60-SO3Li electrolyte material did not show a significant increase, indicating that the electrochemical stability window of the material is as high as 4.54V. Fig.16 As shown, it shows potential for application in high-voltage electrode system lithium-ion batteries.

[0092] Although the detailed process flow of the present invention is described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative, i.e., it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Under the enlightenment of the present invention, those skilled in the art can also make many improvements and changes without departing from the purpose of the present invention, such as equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all of which are within the protection of the present invention.

Claims

1. A defective covalent organic framework material, characterized in that: The covalent organic framework material comprises components including C3 type aldehyde organic monomer, C3 type amino organic monomer and unilateral amino organic monomer, the functional group molar ratio of the C3 type aldehyde organic monomer to the C3 type amino organic monomer and the unilateral amino organic monomer is 1:1, the functional group molar ratio of the C3 type amino organic monomer to the unilateral amino organic monomer is 4:1-2:3, and is prepared based on a three-component co-condensation reaction; the covalent organic framework material has a pore size distribution of 1.0-5.0nm and a specific surface area of ​​60-800m 2 g -1 .

2. The defective covalent organic framework material according to claim 1, characterized in that: The C3 type aldehyde organic monomer is 1,3,5-tri(p-formylphenyl)benzene or 2,4,6-tri(4-aldehydephenyl)-1,3,5-triazine; the C3 type amino organic monomer is 1,3,5-tri(4-aminophenyl)benzene; the unilateral amino organic monomer is one of aniline, 4-aminobiphenyl, 3',5'-diphenylbiphenyl-4-amine, and 5-phenyl-[1,1:3,1-terphenyl]-4,4-diamine.

3. The defective covalent organic framework material according to claim 1, characterized in that: In the three-component co-condensation reaction, the mixed solvent used is an organic solvent that can mix the above three organic monomers to form a uniform dispersion, and the organic solvent is a combination of one or more of dioxane, n-butanol / o-dichlorobenzene and mesitylene / dioxane; the catalyst is an acetic acid aqueous solution with a molar concentration of 3M to 9M.

4. A method for preparing a covalent organic framework material according to any one of claims 1 to 3, characterized in that: The steps include: Step 1) weighing the molar ratio of each component functional group of the C3 type aldehyde organic monomer, the C3 type amino organic monomer and the unilateral amino organic monomer, and weighing the mixed solution and the catalyst according to the molar volume concentration of the total amount of organic monomer and the mixed solvent and the total amount of organic monomer and the catalyst are 1mmol / mL respectively; Step 2) The three organic monomers and the mixed solvent weighed in step 1) are placed in an ampoule, mixed evenly under ultrasonic conditions, and then the catalyst weighed in step 1) is added to carry out a polycondensation reaction based on a three-component co-condensation strategy through a solvent thermal reaction to prepare a defective covalent organic framework material containing aldehyde active anchor points.

5. The preparation method according to claim 4, characterized in that: In step 2), the process conditions of the solvent thermal reaction are: The reaction is carried out in an oven at a reaction temperature of 90-150° C. for a reaction time of 24-96 hours. After the reaction is completed, a precipitate is obtained at the bottom of the ampoule bottle. After the precipitate is subjected to a post-treatment reaction, a defective covalent organic framework material containing an aldehyde active anchor point is obtained. The post-treatment process is: cooling the precipitate to room temperature, collecting the precipitate with a centrifuge tube, and then washing it with tetrahydrofuran, methanol and acetone for multiple times until the solution is colorless, and the product obtained by drying is a yellow solid powder; purifying by Soxhlet extraction, extracting with tetrahydrofuran for 12-96 hours, and then vacuum drying the obtained polymer for 24-48 hours.

6. The preparation method according to claim 5, characterized in that: In step 2), in the solvent thermal reaction, the reaction temperature is 120° C. and the reaction time is 72 hours.

7. The preparation method according to claim 5, characterized in that: In step 2), the Soxhlet extraction method is used for purification, the tetrahydrofuran extraction time is 24 hours, and the obtained polymer is vacuum dried for 24 hours.

8. An application of a defective covalent organic framework material prepared by the preparation method according to any one of claims 4 to 7, characterized in that: The defective covalent organic framework is used to prepare solid electrolyte materials.

9. The use of the defective covalent organic framework material according to claim 8, characterized in that: The defective covalent organic framework material is functionally modified based on a functionalization reaction method, and a functional covalent organic framework material is prepared by a Schiff base reaction and an ion exchange reaction in sequence. The solid electrolyte material is prepared by a tabletting method on the activated functional covalent organic framework material.

10. The use of the defective covalent organic framework material according to claim 9, characterized in that: The defective covalent organic framework material is functionally modified based on the functionalization reaction method. The defective covalent organic framework material is used as a matrix. A functional small molecule 3-aminopropane sulfonic acid with an amino functional group is introduced through a Schiff base reaction. The functional small molecule is used as a molecular group for improving lithium ion conduction. The sulfonic acid group is exchanged with a lithium sulfonate group through an ion exchange reaction to obtain a functional covalent organic framework material. The steps are as follows: The defective covalent organic framework material and the functional small molecule are added to the reaction bottle at a molar ratio of 1:1.2, and an appropriate amount of anhydrous ethanol is added as a reaction solvent, and the mixture is heated to 80°C for reaction for 12 hours, and the precipitate is collected with a centrifuge tube, and the unreacted functional small molecules are removed by washing with ethanol for multiple times, and then dried to obtain a bright yellow solid powder intermediate product; The intermediate product and a 5M LiOAc aqueous solution were added to a reaction bottle at a mass volume ratio of 50 mg / 20 ml, and stirred at room temperature for 72 hours. After the reaction was completed, the precipitate was collected, centrifuged and washed with deionized water several times, and the yellow solid powder obtained by drying was the functional covalent organic framework material.

Citation Information

Patent Citations

  • Lithiation covalent organic framework composite polymer electrolyte as well as preparation and application thereof

    CN112786960A

  • Defect-rich covalent organic framework material, preparation method thereof and application thereof in photocatalytic hydrogen evolution

    CN113896851A

  • Electrodeposition preparation method and application of ionic covalent organic framework nanosheet protective layer

    CN115010941A